Metafora konseptual aksara Jawa dalam Serat Centhini: kajian linguistik kognitif - Elika, Ninik; Nurhayati, Nurhayati (Universitas Mulawarman, 2024)
This research aims to describe the conceptual metaphor of the Javanese character in Serat Centhini. Serat Centhini is the most extensive literary work formed by the Javanese song on Java and was written in Javanese characters using the Old Javanese language. Volume 3, part 5 of Serat Centhini explores the conceptualization of the Japanese character as it relates to the history of the emergence of life, body parts, and mortality. This research uses qualitative descriptive paradigm methods, utilizing gathering and interview techniques. The theoretical framework is based on the Lakoff and Johnson theory. The research results show us that Javanese people conceptualize the history of life’s emergence, body parts, and mortality into Javanese characters based on visual similarities, location or position, the sound of the characters, and their meanings. This conceptualization also reflects the acculturation of Javanese culture with Islam and the relationship between humans and God.